2017
DOI: 10.1111/sode.12241
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of coping self‐efficacy beliefs on the relationship between parental conflict and child psychological adjustment

Abstract: The effect of parental conflict on children's psychological adjustment is variable. Coping self-efficacy refers to a person's perceived ability to self-motivate and access the required cognitive resources to take control of, or exert their coping efforts in a stressful situation. This study investigated the mediating role of children's coping self-efficacy beliefs between parental conflict and children's psychological adjustment (internalizing, externalizing, anxiety, and prosocial behavior). The participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 67 publications
(78 reference statements)
1
8
0
Order By: Relevance
“…Psychological resources, such as self-efficacy, have been found to affect individual responses to traumatic events. Self-efficacy has been found to be associated with positive psychological adjustments that protect adolescents from the negative impacts of parental conflict (Brummert Lennings & Bussey, 2017), community violence (Darawshy & Haj-Yahia, 2018), earthquakes (Ho et al, 2017), and terrorist attacks (Benight et al, 2000). Social posttraumatic recovery cognitive theory claims that a strong sense of self efficacy strengthens a person's resilience to adversity (Benight & Bandura, 2004).…”
Section: Moderating Role Of Self-efficacymentioning
confidence: 99%
“…Psychological resources, such as self-efficacy, have been found to affect individual responses to traumatic events. Self-efficacy has been found to be associated with positive psychological adjustments that protect adolescents from the negative impacts of parental conflict (Brummert Lennings & Bussey, 2017), community violence (Darawshy & Haj-Yahia, 2018), earthquakes (Ho et al, 2017), and terrorist attacks (Benight et al, 2000). Social posttraumatic recovery cognitive theory claims that a strong sense of self efficacy strengthens a person's resilience to adversity (Benight & Bandura, 2004).…”
Section: Moderating Role Of Self-efficacymentioning
confidence: 99%
“…First, most of the previous literature is strongly characterized by studies based on data from the United States (e.g., Kouros et al, 2010;McCoy et al, 2013;Miga et al, 2012). Only few studies have documented the detrimental effects of family conflict in non-US contexts that range from various mental problems in adolescents in Hong Kong, Turkey and Egypt (Elemary et al, 2016;Koçak et al, 2017;Low, 2021), and lower self-control skills in Japanese children (Hosokawa & Katsura, 2017) to more internalizing and externalizing problems in children from Australia (Brummert Lennings & Bussey, 2017) and poorer academic performance in children from the UK (Harold et al, 2007), for example.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…Arguments and conflicts are an inevitable part of family life, and inter-parental conflicts are one of the most prominent, parent-driven factors that negatively influence the home environments of children and adolescents (e.g., Brock & Kochanska, 2016;Brummert Lennings & Bussey, 2017;Hosokawa & Katsura, 2017;Troxel & Matthews, 2004;Vandewater & Lansford, 1998). Conflicts between parents have been identified repeatedly in the literature as crucial risk factors for children's mental health, behavioral and emotional problems, and social behavior (e.g., Auersperg et al, 2019;Davies et al, 2016;McCoy et al, 2009;O'Hara et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Ample research before the COVID-19 pandemic identified risk factors for family dysfunction. Those general factors associated with family dysfunction include high family conflict [ 11 ], poor parenting practices [ 12 , 13 ] and poor parent–child relationships. Deprived families, for example those living in poor neighborhoods [ 14 ] or experiencing economic pressure [ 15 ], are often among those with heightened levels of dysfunction.…”
Section: Introductionmentioning
confidence: 99%